PEMBERDAYAAN DAN PELATIHAN REMAJA MESJID AL-ALI SEBAGAI AGEN MODERASI BERAGAMA - Ahsani Amalia Anwar; Nurlaila Tuanany; Belly Isayoga Kristyowidi; Muis S.A. Pikahulan; Ajuan Tuhuteru; Ferry Rangi (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Understanding of religious teachings is something that must be done by every adherent. This understanding is not only about the teaching itself but also understanding the various interpretations of the teaching. When a person can understand the various interpretations that exist, he will be more likely to take the middle path (moderate) from what he understands. An extreme attitude in understanding religious values ​​will emerge when a believer of a religion has no alternatives. This activity was carried out by identifying the problems faced by youth of the Al Ali mosque in internalizing the notion of religious moderation, so PkM activities were held with the theme "Empowerment and training of Youth of the Al-Ali Mosque as Agents of Religious Moderation" as well as providing a briefing on strategies and tactics for spreading inclusive religious understanding . Increasing the understanding of religious moderation among mosque youth is very important so that youth in mosques can realize that religion is their innate nature which must be actualized in this life. So that mosque youth can develop multicultural and multireligious insights both within the mosque and in the community, intensify community-based dialogue between religions, and involve the younger generation/millennials to organize cross-cultural and religious socio-economic activities.